Analisis Persepsi Mahasiswa terhadap konsep Meritokrasi Manajemen Pendidikan untuk Mencegah Nepotisme dalam Rekrutmen Guru Sekolah Dasar - Fitri Mardayanti; Aribah capah; Khofifah Indah T; Septi Qorima Sitorus; Tryona Loise Siahaan; Agum Budianto (RISOMA : Jurnal Riset Sosial Humaniora dan Pendidikan, 2025)
This study aims to analyze students' perceptions of the concept of meritocracy in education management as an effort to prevent nepotism in the recruitment process for elementary school teachers. Meritocracy is seen as an approach that emphasizes individual competence, qualifications, and achievements in the selection process for educators, while nepotism is often an obstacle in creating a professional and ethical educational environment. This study uses a quantitative descriptive method with data collection through questionnaires distributed to students in education study programs who have acquired a basic understanding of educational management and teacher recruitment systems. The data were analyzed to describe the students' level of understanding, attitudes, and views on the application of meritocracy principles and their awareness of the negative impacts of nepotism in the world of education. The results show that the majority of students have a positive perception of meritocracy as a fair and effective system for improving the quality of educators. However, some students acknowledge that nepotism is still common in the education sector and is considered to undermine professionalism and public trust. These findings emphasize the importance of instilling meritocratic values from the university level and strengthening competency-based recruitment policies to support the creation of a transparent and high-quality education system.